ANALYSIS OF THE LINGUISTIC FOUNDATIONS OF UZBEK - ENGLISH THROUGH ARTIFICIAL INTELLIGENCE - Raxmanova Azizaxon Abdugafurovna (Journals Park Publishing, 2024)
This article explores Uzbek-English language dynamics through artificial intelligence. It separates historical backgrounds, syntactic structures, semantic maps, and translation barriers. Through AI, it provides insight into addressing linguistic gaps, demonstrating the potential of technology in improving intercultural communication and understanding.
Keywords: Uzbek-English translation, linguistic analysis, historical context, syntactic analysis, semantic mapping, AI-driven technologies.